Evaluating the applicability of an alkaline amino acid leaching process for base and precious metal leaching from printed circuit board waste - Broeksma, Cara Philipa (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.